Industrial education - Peterson, Charles John (My University, 1893)
Introduction: The term industrial education is used in more than one sense, and therefore does not convey the same idea to all minds. The general significance is the application of art and science to our useful pursuits. Of late this has been a theme of much discussion, which causes us to ask why? Early in civilization each individual contributed almost wholly to his own wants, which were few, and simple, but as the community progresses division of labor takes place, and as a consequence more skill is required to meet this demand certain time must be had in experience or practice before the duties of each occupation can be assumed. Among the early methods for fitting the youth for different trades was the apprenticeship. When this was prevalent there was no such thing as industrial schools.
Citation: Peterson, Charles John. Industrial education. Senior thesis, Kansas State Agricultural College, 1893.
Morse Department of Special Collections
Keywords: Industrial education; Youth; Divisions of labor; Theses; Manuscripts (documents)